Functionalized carbon nanotube reinforced polymer nanocomposite microcapsules with enhanced stiffness - Jagtap, Siddheshwar B.; Patil, Vishal D.; Suresh, Karthika; Ram, Farsa; Mohan, Muthu Subramanian; Rajput, Shatruhan S.; Patil, Shivprasad; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2018)
Microcapsules with tunable mechanical properties are highly desirable in pressure sensitive applications. We report here a facile approach to prepare polyurea/multiwall carbon nanotube (MWCNTs) nanocomposite microcapsules (MICs) with enhanced stiffness. A model compound dimethyl phthalate (DMP) was used as core material. MWCNTs were modified with reactive functional groups namely carboxyl (-COOH), amines (-NH2), and isocyanates (-NCO) to ensure a stronger interface between polymer wall and MWCNTs. Functionalization of MWCNTs was corroborated by Fourier transformed infrared spectroscopy (FTIR). Scanning electron microscopy (SEM) was employed to study the surface morphology of MICs. The presence of MWCNTs in the microcapsule wall was confirmed by transmission electron microscopy (TEM). MICs with functionalized MWCNTs show almost 100% increase in stiffness with respect to pristine capsules. All MICs show 92-97 +/- 1% encapsulation efficiency. The approach used in this paper can be broadly utilized to tune the mechanical properties of the microcapsules.

Tuning controlled release behavior of starch granules using nanofibrillated cellulose derived from waste sugarcane bagasse - Patil, Mayur D.; Patil, Vishal D.; Sapre, Aditya A.; Ambone, Tushar S.; Torris, Arun A. T.; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (ACS Sustainable Chemistry & Engineering, 2018)
Controlled release formulations help to encapsulate agrochemicals and deliver at a sustained rate. Growing environmental challenges have increased the need for controlled release systems based on sustainable feed-stocks. To this end, we report here the preparation and properties of a monolith-type controlled release granular formulation based on two ubiquitous biopolymers, starch and cellulose. Cellulose nanofibers (CNFs) derived from waste sugarcane bagasse were mixed with gelatinized maize starch and urea formaldehyde to yield nanocomposite granular formulation. Dimethyl phthalate (DMP) was used as model encapsulant. The morphology of CNFs and CNFreinforced starch granules was characterized by transmission electron microscopy, scanning electron microscopy, BET porosimetry, and X-ray tomography. Incorporation of only 2-4 wt % CNFs led to a significant reduction in porosity as compared to that for neat starch granules, while the water uptake was enhanced by 20-30%. Reinforcing starch with CNFs led to a significant reduction in initial release rate and yet higher overall release of DMP, thereby allowing effective utilization of entrapped chemicals. This interesting release behavior could be attributed to two competing factors, water uptake-induced diffusion and barrier effects rendered by nanocellulose network.

Sustained release insect repellent microcapsules using modified cellulose nanofibers (mCNF) as pickering emulsifier - Kadam, Sandip L.; Yadav, Prashant; Bhutkar, Siddhant; Patil, Vishal D.; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2019)
We report here an approach to encapsulate N, N-diethyl-3-methylbenzamide (DEET), an insect repellent, through interfacial polycondensation using modified cellulose nanofiber (CNF) as pickering emulsifier. We found that stearic acid functionalized CNF (mCNF) can be used to form stable pickering emulsions (oil-in-oil and water-in-oil), and further encapsulate DEET using interfacial polycondensation with very high encapsulation efficiency of about 98%. Another major advantage of this approach is that mCNF can act both as pickering emulsifier and also strengthen the barrier properties of microcapsules resulting in significant reduction in release rate of DEET. Interpretation of the release profiles using standard mathematical models proposed by Ritger-Peppas show a factor of three reduction in release rate constant for the microcapsules reinforced with mCNF.
Keywords: Cellulose nanofiber; Controlled release; Microcapsules; Nanocomposite; nanoparticle; Pickering emulsion